Adaptive differential evolution and pattern search tuned fractional order fuzzy PID for frequency control of power systems. (4th March 2022) - Mohanty, Prangya; Sahu, Rabindra Kumar; Sahoo, Dillip Kumar; Panda, Sidhartha
ABSTRACT: In the fast-growing dimension and difficulty of the electricity network, frequency regulation (FR) is considered to be the major significant choice for presenting superior quality electric power supply to the customers. Load-frequency control (LFC) scheme involves greatly vital, capable and intelligent control method to carry a strong power under the erratic nature of consumers' demand. Thus, in this study proposes a hybrid Adaptive Differential Evolution and Pattern Search (hADE-PS) tuned Fractional Order Fuzzy PID (FOFPID) structure for FR of power systems (PSs). Firstly, a three unequal area system is taken and results of hADE-PS tuned FOFPID is compared with Teaching Learning-Based Optimization (TLBO) and Firefly Algorithm (FA) based controllers for the identical test systems. Then, the robustness of FOFPID is examined under varied conditions. In the next step, a power system with thermal and solar power is considered. The results of hADE-PS tuned FOFPID are evaluated with Genetic Algorithm (GA), FA, Whale Optimization Algorithm (WOA) and modified WOA for the same test system. It is demonstrated that hADE-PS-based FOFPID controller is more effective compared to some lately proposed methods. To substantiate the practicability of the projected method, experimental justification utilizing OPAL-RT-based real-time simulation has been carried out.